2022
DOI: 10.1248/bpb.b22-00245
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Pharmacist Team Clinical Medication Review in Older Adults: A Prospective and Retrospective Observational Study

Abstract: Polypharmacy in older adults causes problems such as increased adverse drug reactions, overdose or duplication, and poor medication adherence. We have established a "medication review team" organized by pharmacists. This prospective and retrospective observational study evaluated the effectiveness of the pharmacist-led team-based approach for reducing polypharmacy as compared to the individual pharmacist approach. Data on the individual pharmacist approach were collected retrospectively, but prospectively for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…37) Identifying unnecessary medications would also result in a reduction in medical expenditure. 10,38) This study had several limitations. First, causal relationships could not be clarified because this was a cross-sectional study.…”
Section: Discussionmentioning
confidence: 97%
“…37) Identifying unnecessary medications would also result in a reduction in medical expenditure. 10,38) This study had several limitations. First, causal relationships could not be clarified because this was a cross-sectional study.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with previous studies that have demonstrated the importance of a pharmacist-led medication review in a multidisciplinary team. [27][28][29] In a Slovenian study involving psychogeriatric outpatients, pharmacists proposed 374 psychopharmacotherapy interventions (61.5% drug discontinuations, 28.6% drug initiations, and 10.9% dose adjustments) and the physicians accepted 45.2% of them. The interventions reduced the total number of medications per patient, PIMs, potential drug-drug interactions, and resulted in greater adherence to treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Renal disease is frequently accompanied by hypertension and diabetes mellitus, among other chronic conditions; therefore, the patient's conditions are more complicated, requiring the use of multiple medications and increasing the risk of drug interactions. The dose of medicine should be adjusted according to the patient's renal function and administered with great care [1]. The increase in the quantity and diversity of medications consumed by patients not only decreases compliance but also elevates the prevalence of drug-related problems (DRPs).…”
Section: Introductionmentioning
confidence: 99%